OBJECTIVE AND QUANTITATIVE ESTIMATION OF THE OPTIMAL TIMING FOR EPIRETINAL MEMBRANE SURGERY ON THE BASIS OF METAMORPHOPSIA. Issue 4 (April 2022) - Kanzaki, Yuki; Doi, Shinichiro; Matoba, Ryo; Kanzaki, Sayumi; Kimura, Shuhei; Hosokawa, Mio M.; Shiode, Yusuke; Takasu, Ippei; Morizane, Yuki
Abstract : Supplemental Digital Content is Available in the Text. We examined the relationship between maximum depth of retinal folds and metamorphopsia in epiretinal membrane and showed that maximum depth of retinal folds is an objective and quantitative biomarker of metamorphopsia. Our results suggest that the quality of vision could be maintained if epiretinal membrane is removed when the preoperative maximum depth of retinal folds is 69 µ m to 118 µ m. Abstract : Purpose: To establish an objective and quantitative biomarker of metamorphopsia in epiretinal membranes (ERMs) and determine the optimal timing for ERM surgery. Methods: Retrospectively, 172 eyes with ERM were reviewed. Retinal folds because of tangential traction by ERM were visualized by en-face optical coherence tomography. The maximum depth of retinal folds (MDRF) within the parafovea was quantified. Metamorphopsia was quantified by M-CHARTS. The change in the distance between the retinal vessels after ERM surgery and the preoperative total depth of retinal folds between the vessels were quantified using en-face optical coherence tomography and optical coherence tomography angiography. Results: Significant correlations were observed between preoperative MDRF and M-CHARTS scores before and at 6 months after surgery (r = 0.617 and 0.460, respectively; P < 0.001) and change in the distance between the retinal vessels after ERM surgery and preoperative total depth of retinal folds between the vessels ( r = 0.471; P = 0.013). The preoperative MDRF values at which M-CHARTS scores were 0.5 before and 6 months after the surgery were 69 µ m and 118 µ m, respectively. Conclusion: The MDRF is an objective and quantitative biomarker of metamorphopsia in ERM. To maintain patients' quality of vision, ERM surgery may be performed when the preoperative MDRF ranges between 69 µ m and 118 µ m.